Affective Processing in Non-invasive Brain Stimulation Over Prefrontal Cortex - Liu, Wei; Leng, Ya Shu; Zou, Xiao Han; Cheng, Zi Qian; Yang, Wei; Li, Bing Jin (Frontiers in Human Neuroscience, 2017)
The prefrontal cortex is the most frequently targeted brain region by non-invasive brain stimulation studies. Non-invasively stimulating the prefrontal cortex has been shown to both modulate affective processing and improve the clinical symptoms of several psychiatric disorders, such as depression and schizophrenia. The magnitude of the modulation depends on several factors, including the stimulation frequency, the number of stimulation sessions, and the specific sub-region of the prefrontal cortex that is stimulated. Though some of the potential underlying mechanisms have been identified, the exact mechanisms that underlie these cognitive and affective changes remain unclear. The present review aims to summarize recent advances in the study of affective processing using non-invasive brain stimulation of the prefrontal cortex. We will provide a theoretical framework for better understanding how affective processing changes are induced by non-invasive brain stimulation, with the goal of providing testable hypotheses for future studies.